Use of Human Umbilical Cord Serum to Treat Animal Skin Burns - Kassab, Hanan J.; MERDAW, Maysoon A.; J. Al- Ramahi, Intesar; A. Alasadi, Alaa; Al Mousauy, Sawsan; Ahmed, Rownak; Ismaeel, Israa; Al-Sultani, Dorees (Iraqi Journal of Pharmaceutical Sciences, 2019)
Objective: The objective of the study was to test the hypothesis, that umbilical cord blood crude serum applied topically with its high concentration of growth factors may promote an early healing for animal models with burn injury.Methods: Fresh human umbilical cord blood UCBS was collected and screened for transmitted diseases such as hepatitis B, hepatitis C and HIV. Mice and rabbits were scalded by boiling water and chemical burning by NaOH, then treated with UCBS. In comparison with a Cetrimide treated group and a control group (without treatment). The UCBS was subjected to microbial testing to demonstrate the presence or absence of extraneous viable contaminating microorganisms.Results: Topical application of UCBS promoted the healing process; complete healing was seen after 10 days for the mice group and in 7 days in the rabbit group. Cetrimide group applied to the rabbit showed slow healing and needed 10 days for hair regrowth. Control group in both mice and rabbits showed very slow response and the burn area diameter remained the same for over 10 days, and no hair regrowth was obvious after 10 days. Conclusion: The results of the current study indicated that UCBS is a promising therapy for the healing of burns by boiling water and/or chemical substance, more clinical trials are needed to further explore the long-term effects after UCBS use.